Identifying corridors for Asiatic black bear (Ursus thibetanus) in a part of Eastern Himalayas, India - Bhattacharya, Malyasri; Sarkar, Debanjan; Pandey, Sneha; Mondal, Indranil; Sathyakumar, Sambandam; Kumar, R. Suresh; Talukdar, Gautam (Frontiers in Conservation Science, 2025)
The Asiatic black bear (Ursus thibetanus), classified as a vulnerable species on the IUCN Red List, is an important mammal species found in the state of Sikkim, India. Studies carried out in Khangchendzonga National Park have documented the presence of these bears, highlighting their crucial conservation importance in the region. The population of Black bears are restricted to small habitat patches, which over the years have become fragmented by road networks and urban settlements. In such fragmented landscapes, connecting corridors play a crucial role in maintaining wildlife movement and genetic diversity. We assessed connectivity between eight protected areas in Sikkim using MaxENT and Circuitscape. 65 black bear presence locations (collected through Camera traps and sign surveys) and 24 environmental variables were used to model the corridors. Habitat suitability map was generated through MaxENT modelling approach. Our analysis suggests that there are multiple options to maintain connectivity for black bears in Sikkim. We mapped seven corridors and five pinch points (bottlenecks in connectivity), and calculated metrics to estimate their quality and importance. Our model output was supported by high AUC value (0.921) and field validation by questionnaire surveys and sign surveys to assess black bear presence and habitat use. Our results showed that 300 km² of the suitable regions are within the protected areas in Sikkim. The highest quality linkages as measured by the ratio of cost-weighted distance to Euclidean distance (CWD:EucD) and cost-weighted distance to least-cost path (CWD:LCP) were Khangchendzonga and Barsey, suggesting that these protected areas (National Parks and Wildlife Sanctuaries) and the developed corridors play important role in maintaining connectivity. We mapped pinch-points which are habitat where black bear movement is restricted due to unfavorable environments, linear infrastructures, built up/settlements or a combination of factors and our model predicted pinch points near few settlement areas; Mangan, Dikchu, Pangthang, Kabi, Yuksum and Lachen. Ground truthing confirmed that these areas also coincide with Black bear conflict zones in Sikkim.